Knowledge regarding Teenage Pregnancy among Adolescene Girls of Secondary School of Sindhuli - Shrestha, Rupa Laxmi; Khadka, Laxmi (Nepal Medical College Journal, 2022)
Teenage pregnancy is a global problem mostly occurring in poor and marginalized community. Teenage pregnancy increases when girls are denied the right to make decisions about their sexual and reproductive health and well-being. The objective of this study was to assess knowledge regarding teenage pregnancy among adolescence girls of secondary school. A descriptive cross sectional study was conducted with sample size of 100 by using probability stratified sampling technique. Pretested (r=0.74) structured and semi structured questionnaires (lowest 1 and highest score 34) were used as instrument for data collection. Data was collected through self administered technique. Data analysis was done from descriptive (mean, SD, frequency, percentage) and inferential (independent t test, ANOVA test) statistics using SPSS version 16. The findings of the study showed that respondents were age group 13-15 years (51%), hindu (91%), chhetri (36%), class 9 and 10 (41%) and family (71%) as a source of information. The overall mean knowledge score of respondents was 25.81±3.46 with the minimum score 14 and maximum score 34. The mean knowledge about contributing factors was 12.34±1.82, consequences were 6.69±1.82 and preventive measures were 6.78±1.17. The knowledge score regarding teenage pregnancy was significant in relation to age and education status of respondents where p value were 0.002, 0.000 respectively. It is concluded that respondents had adequate knowledge. According to findings, teenage pregnancy awareness program should be carried out in school and community through mass media to prevent teenage pregnancy in adolescence.